PELATIHAN SERVICE SEPEDA MOTOR INJEKSI PEMUDA DESA BANDAR SETIA KABUPATEN DELI SERDANG - Yulanto, Dwiki Muda; Basuki, Nur; Doni, Rahma (Jurnal Abdi Insani, 2025)
According to the results of observations that have been carried out, especially regarding the last level of education in Hamlet 3, Bandar Setia Village, it shows that the majority of youth in Hamlet 3, Bandar Setia Village have a low level of education. The low level of education of the community in Hamlet 3, Bandar Setia Village is one of the factors that influences the low quality of welfare or the low level of the hamlet/village economy. Another problem faced by partners is that many young people drop out of school at a productive age who do not have special/additional skills so they do not have the opportunity to find promising work or do not have the opportunity to open their own business/entrepreneurship. Seeing the increasing number of motorbikes and many young people in Hamlet 3, Bandar Setia Village have an interest in the automotive sector, especially motorbikes. Therefore, the PkM team has carried out several activities to overcome these problems, namely (1) providing training on injection motorbike service (electronic fuel injection); (2) providing entrepreneurial training related to motorbike repair shops. The method of implementing this activity starts from socializing activities, implementing training, monitoring and evaluation. After participating in the training, partners felt that there was an increase in knowledge and skills related to injection motorbike service. Furthermore, partners are increasingly encouraged to own their own repair shops. Such activities can help improve the skills and well-being of the community.